Sintering, Electrical Conductivity, Oxygen Nonstoichiometry, Thermal Expansion and Thermal Stability of Ruddlesden-Popper Type Cobaltite La4Co3O10. Issue 9 (16th July 2016) - Adachi, Yoshinobu; Hatada, Naoyuki; Uda, Tetsuya
Abstract : A favorable cathode performance can be expected with La4 Co3 O10, due to the similarity to the representative cathode material of LaCoO3 . However, its narrow stable oxygen partial pressure ( p O2 ) range has made it difficult to synthesize and sinter La4 Co3 O10, and its electrical and ionic properties has not yet been studied enough. In this study, the dense body of La4 Co3 O10 was prepared by controlling p O2 during sintering within its stable range utilizing the equilibrium between Fe2 O3 and Fe3 O4 . The electrical conductivity of La4 Co3 O10 is comparable to those of perovskite-type cathode materials such as LSCF. And its oxygen nonstoichiometry is hyperstoichiometric. Additionally, it was revealed that in air La4 Co3 O10 partially decomposes to LaCoO3 and La2 O3 in 100 h at 800°C or higher, while no decomposition product was detected by X-ray diffraction at 700°C or lower.